Nickel-Catalyzed Enantioconvergent C(sp3)–C(sp3) Cross-Coupling between α-Iodogermanes and Alkylzinc Reagents - Acuña-Bolomey, Emilio G. A.; Oestreich, Martin (Synthesis, 2025)
We report a nickel-catalyzed enantioconvergent C(sp3)–C(sp3) cross-coupling between α-iodogermanes and alkylzinc reagents to access α-chiral alkylgermanes. This transformation, a strategy previously established for silicon-based electrophiles, extends to germanium, enabling the enantioselective formation of α-chiral germanes from simple, unactivated alkyl chains. While yields and enantioselectivities remain moderate, the reaction outcome was finely tuned through the design and evaluation of a library of over 30 ligands, including more than a dozen novel scaffolds. Notably, two distinct NiBr₂∙PyBox complexes allowed for access to products of opposite absolute configuration, and preformed nickel complexes were required to reach synthetically useful conversions. These findings highlight the challenges of asymmetric catalysis with heavier main-group elements and provide a platform for the future design of ligands tailored to organogermanium chemistry.
Keywords: Asymmetric catalysis; C(sp3)–C(sp3) cross-coupling; Enantioconvergence; Germanium; Nickel